Game over or jumping to the next level? How playing the serious game "Mobility Safari" instigates social learning for a smart mobility transition in Vienna. - Gugerell, Katharina; Platzer, Mario; Jauschneg, Martina; Ampatzidou, Cristina; Berger, Martin (Springer, 2018)
Serious games and gaming are increasingly considered as the magic bullet for improved stakeholder involvement and citizen engagement in urban planning and governance. They are also discussed as means to instigate learning and capacity building and to raise the awareness of citizens and stakeholders about various urban topics. These learning processes can unfold in various different formats, such as social or game-based learning. This chapter investigates if playing the serious game prototype Mobility Safari supports such processes. Mobility Safari is a serious-game prototype developed for the City of Vienna. The game is targeting Vienna s ambition to become a smart city. One focal point of this ambition concerns the change towards a more sustainable mobility system. Our analysis illustrates that the serious game indeed evokes learning processes during the gameplay and the debriefing, covering a broad range of learning activities and social interaction. Incomplete rule-sets and un-governed situations trigger discussions in which players confront the game experience with their actual real-world practices. Our analysis suggests that games are indeed suitable means for informing citizens and supporting capacity-building processes in participatory-planning approaches. However, they need a careful design, facilitation and sufficient time for a debriefing so that players can reflect on the game experience. This reflection is crucial to transform the game experience into a deeper learning experience that is meaningful for real-world contexts.
Keywords: Mobilität; Wissensvermittlung; Stadtpolitik; Bürgerbeteiligung; Smart City; Planungsprozess; Spiel